2021
DOI: 10.1111/jan.14926
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing initiation of health behaviour conversations with patients: Cross‐sectional study of nurses, midwives, and healthcare support workers in Wales

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…In contrast to the positive view of participants towards their GP, a systematic review showed that GPs do not feel responsible for weight management and perceive numerous barriers, including a lack of consultation time 20 . Other studies found that GPs are often reluctant to approach weight management discussions for fear of causing embarrassment or compromising the doctor–patient relationship 53,54 . However, GPs have an important role as educators and supporters by providing advice and encouraging and motivating their patients to lose weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the positive view of participants towards their GP, a systematic review showed that GPs do not feel responsible for weight management and perceive numerous barriers, including a lack of consultation time 20 . Other studies found that GPs are often reluctant to approach weight management discussions for fear of causing embarrassment or compromising the doctor–patient relationship 53,54 . However, GPs have an important role as educators and supporters by providing advice and encouraging and motivating their patients to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies found that GPs are often reluctant to approach weight management discussions for fear of causing embarrassment or compromising the doctor-patient relationship. 53,54 However, GPs have an important role as educators and sup- Participants found it difficult to adhere to a lifestyle intervention when family members were not supportive. A spouse who buys unhealthy food, children who seek attention, and family members who do not take the weight management challenge seriously all hinder individuals who want to lose weight.…”
Section: Interpretation Of Findings In Relation To Existing Literaturementioning
confidence: 99%
“…Furthermore, current clinical guidelines endorse the delivery of behaviour change interventions to reduce the incidence of chronic diseases (National Institute for Health and Clinical Excellence, 2014). While we know that health care professionals have previously reported a lack of confidence and competence in holding health behaviour change conversations with patients (Bright et al, 2021), it has been shown that it is possible to significantly improve confidence, T A B L E 4 Logistic regression of predictor variables associated with the primary outcome, having delivered a MECC intervention (with significant predictors in bold font). competence and intention to deliver behaviour change interventions as a result of skills training (Bull & Dale, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This focus can enhance the clinical treatment effect and earn patients' and patient families' acceptance of hospital nursing work. 16,17 At the same time, this nursing method encourages patients to participate actively in the treatment of the disease and raises patients' awareness of self-care, 18,19 in contrast with passive acceptance of treatment. In this way, patients better accept and comply with treatment measures.…”
Section: Discussionmentioning
confidence: 99%